On the move to meaningful internet systems: OTM 2011 workshops Confederated International Workshops and Posters: EI2N+NSF ICE, ICSP+INBAST, ISDE, ORM, OTMA, SWWS+MONET+SeDeS, and VADER 2011, Hersonissos, Crete, Greece, October 17-21, 2011. Proceedings - Meersman, Robert; Dillon, Tharam S. 1943-; Herrero, Pilar 1959- (Lecture Notes in Computer Science, 2011)
This volume constitutes the refereed proceedings of nine international workshops, EI2N+NSF ICE, ICSP, INBAST, ISDE, MONET, ORM, SeDeS, SWWS, and VADER 2011, held as part of OTM 2011 in Hersonissos on the island of Crete, Greece, in October 2011. The 64 revised full papers presented were carefully reviewed and selected from a total of 104 submissions. The volume also includes three papers from the On the Move Academy (OTMA) 2011 and five ODBASE 2011 poster papers. Topics of the workshop papers are enterprise integration and semantics, information centric engineering, interoperability, industrial and business applications of semantic Web applications, information systems in distributed environments, process management in distributed information system development, distributed information systems: implementation issues and applications, industrial applications of fact-oriented modeling, data warehouse modeling, extensions to fact-oriented modeling, model validation procedures, schema transformations and mapping, semantic Web and Web semantics, ontology development, deployment and interoperability, data access and efficient computation, efficient information processing, exchange and knowledge synthesis algorithms, mobile and networking technologies for social applications, semantic and decision support, variability in software architecture, and dynamic and adaptive architectures.